KAJIAN TOTAL BIOMASSA RERUMPUTAN DAN PENGARUHNYA TERHADAP TATA AIR TANAH DI DAERAH TANGKAPAN AIR DANAU TOBA. STUDI KASUS DI KECAMATAN SILAHISABUNGAN KABUPATEN DAIRI - Sahala M Manurung; Abdul Rauf; Razali Razali (Universitas Sumatera Utara, 2013)
The study on the total of biomass of grasses and it’s influences on soil moisture was conducted atSilahisabungan Subdistrict Dairi District, from November 2011 until February 2012. The objectiveof this research was to evaluate the effect of grasses to soil mositure. This study used survey methodwith purposive sampling. The result of this research showed that grass vegetation with rathersloping class total biomass 10,6 ton/ha, carbon reserve 5,3 ton/ha, field capacity 63,4 %, permanentwilting point 1,3 %, water content 62,0 % and permeability 7,5 cm/hours. In the undulating slopestotal biomass 7,1 ton/ha, carbon reserve 3,55 ton/ha, field capacity 51,6 %, permanent wiltingpoint 2,4 %, water content 49,2 % and permeability 7,6 cm/hours. In the rather steep slope totalbiomass 15,5 ton/ha, carbon reserve 7,75 ton/ha, field capacity 32,8 %, permanent wilting point 3,8%, water content 29,0 % and permeability 9,6 cm/hourd. In the forest vegetation with rather slopingclass, biomass total 7,54 ton/ha, carbon reserve 3,77 ton/ha, field capacity 150 %, permanent wiltingpoint 23,5 %, water content 126,5 % and permeability 10,3 cm/hours. In the undulating slopes totalbiomass 6,24 ton/ha, carbon reserve 3,12 ton/ha, field capacity 51,5 %, permanent wilting point 7,5%, water content 44 % and permeability 8,2 cm/hours. In the rather steep slope total biomass 8,86ton/ha, carbon reserve 4,43 ton/ha, field capacity 33,3 %, permanent wilting point 4,2 %, watercontent 29,2 % and permeability 11,25 cm/hours.Key words: biomass, soil moisture, toba lake water catchment area